2021
DOI: 10.3390/v13081581
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Amino Acids in the Pestiviral Erns Control Cell Entry, Endoribonuclease Activity and Innate Immune Evasion

Abstract: The genus Pestivirus, family Flaviviridae, includes four economically important viruses of livestock, i.e., bovine viral diarrhea virus-1 (BVDV-1) and -2 (BVDV-2), border disease virus (BDV) and classical swine fever virus (CSFV). Erns and Npro, both expressed uniquely by pestiviruses, counteract the host’s innate immune defense by interfering with the induction of interferon (IFN) synthesis. The structural envelope protein Erns also exists in a soluble form and, by its endoribonuclease activity, degrades immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We have shown recently that mutation of a variety of amino acids (especially charged residues) in the membrane anchor region of E rns prevents the recovery of infectious viruses, and that at least one defect resulting from these tested exchanges concerns the assembly and budding step of pestiviruses [10,60]. Another recent publication reported that exchanges of positively charged residues in the anchor region can block virus entry and also transport of secreted E rns into target cells [61]. With this knowledge in mind, it is rather likely that isolation of S209C as the only pseudorevertant is not necessarily a consequence of structural aspects but could simply be due to impairment of functions of the E rns membrane anchor by other mutations leading to non-viable viruses.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown recently that mutation of a variety of amino acids (especially charged residues) in the membrane anchor region of E rns prevents the recovery of infectious viruses, and that at least one defect resulting from these tested exchanges concerns the assembly and budding step of pestiviruses [10,60]. Another recent publication reported that exchanges of positively charged residues in the anchor region can block virus entry and also transport of secreted E rns into target cells [61]. With this knowledge in mind, it is rather likely that isolation of S209C as the only pseudorevertant is not necessarily a consequence of structural aspects but could simply be due to impairment of functions of the E rns membrane anchor by other mutations leading to non-viable viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The orange boxes are focusing on the two RNase active sites conserved among most pestiviruses (except for APPV-and Bat-pestivirus), whereas the black box highlights the residue important for RNase activity as identified in this study using E rns of giraffe pestiviruses. The proposed "positive-region" and "heparin-binding-domain" [24] are boxed in blue.…”
Section: Expression and Purification Of Strep-tagged E Rnsmentioning
confidence: 99%
“…For staining of cellular Mx proteins, a primary mouse monoclonal antibody against MxA was used [24]. As a house-keeping protein, β-actin was detected with a mouse monoclonal anti-β-actin antibody (Sigma, Buchs, Switzerland).…”
Section: Western Blotmentioning
confidence: 99%
See 2 more Smart Citations